Relationship Between Family Support For PLWHA and Adherence to Taking Antiretroviral Drugs at the HKBP AIDS Ministry 2022 - Lindawati Tampubolon; Imelda Derang; Sri Ningsih Sitorus (Sean Institute, 2023)
AIDS is a collection of disease symptoms caused by the Human Immunodeficiency Virus. One of the steps taken to tackle AIDS is to increase adherence to taking antiretroviral drugs. The factor that influences adherence to taking antiretroviral drugs is family support. The type of research used is correlational research with a cross sectional approach. Sampling using pursosive sampling with the number of respondents 121 people. Data collection was carried out using a questionnaire and the statistical test used was the Pearson Product Moment at α 0.05. The results showed that there was a significant relationship between family support for PLWHA and adherence to antiretroviral medication at the HKBP AIDS Ministry (p = 0.001). It is hoped that officers and families can work together well in order to provide optimal support to family members infected with HIV/AIDS.